Didactic Possibilities of Practical and Cognitive Competencies of Computer Science Teachers - Kozim Karimovich Kudratov (Euro Asian Journal Publishing, 2023)
Informatics provides didactic opportunities for the development of the practical and cognitive competence of the teacher, mastery of educational activities due to the actual pedagogical factors, knowledge and skills that depend on the subjective motives of the educational process among students, as well as pedagogical and didactic factors, such as qualifications, preparation for practical activities and attitude to academic subjects are manifested, taking into account the abilities and personal experience of an intellectual and motivational teacher. To do this, our study provides for the training of students in the field of informatics of pedagogical universities
Keywords: algorithmic sequence; practical and cognitive; target component